Muscle activation pattern of lower extremity muscles in selected basketball tasks - Chang, H. Y.; Wei, S. H.; Jong, Y. J.; Huang, C. H. (ISB Congress, 2005)
The purpose of this study was to understand the muscle activation pattern of lower extremity muscles during performing specific functional basketball tasks.